2023
DOI: 10.21203/rs.3.rs-2629420/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integration of skin phenome and microbiome reveals the ­key role of bacteria in human skin aging

Abstract: Background: Despite the complexity, distinct ecological niches are believed to primarily drive the skin microbiome composition. Meanwhile, skin aging is a dynamic process with a spectrum of phenotypical changes, making it an attractive model for studying microbiome-phenotype interactions. Although a large number of studies confirmed the impact of chronological age in skin bacterial communities, the understanding of cross-kingdom microbiome variation with skin aging remains minimal. And this is not trivial beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 55 publications
2
4
0
Order By: Relevance
“…The results of this study confirmed some observations previously made using 16S rRNA sequencing studies [24][25][26]28,30,33,42] or using more recent whole-genome sequencing (WGS) studies [27,31,32]. The study results first confirmed that microbial diversity increases during aging [24][25][26][27][28][29]41], largely contributed by shifting Proteobacteria populations and Actinobacteria [24,[28][29][30] or Lactobacillales [43].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The results of this study confirmed some observations previously made using 16S rRNA sequencing studies [24][25][26]28,30,33,42] or using more recent whole-genome sequencing (WGS) studies [27,31,32]. The study results first confirmed that microbial diversity increases during aging [24][25][26][27][28][29]41], largely contributed by shifting Proteobacteria populations and Actinobacteria [24,[28][29][30] or Lactobacillales [43].…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, changes in the microbial functional profile with aging were also reported thanks to deeper functional genomic analyses [25,27,32,35]. Finally, functional evaluation after keratinocytes and fibroblasts treatment by aging-modulated taxa, namely Streptococcus pneumoniae or infantis secretomes [35], or by C. anes and Moraxella osloensis [31], helped to better understand the contribution of those specific taxa to skin aging traits.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present analysis, we focused on samples from cheek skin, which is the key body site for apparent age. More recent studies are shedding additional light on associations of the skin microbiome, notably particular clades of S. epidermidis or C. acnes, with biophysical traits of skin aging, such as collagen quality and quantity (Zhou et al, 2023a;Xia et al, 2023). Our study adds to this nascent, but growing body of knowledge aiming to better understand the implications of the microbiome in skin aging, by identifying the changes associated with signs of skin aging, rather than chronological aging alone.…”
Section: Figurementioning
confidence: 90%